IV.–The Elasticity of Substitution and the Elasticity of Demand for One Factor of Production - Meade, J. E. (Review of Economic Studies, 1934)
Journal Article Notes on the Elasticity of Substitution: IV.—The Elasticity of Substitution and the Elasticity of Demand for One Factor of Production Get access J. E. Meade J. E. Meade Hertford College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 152–153, https://doi.org/10.2307/2967624 Published: 01 February 1934